Sosialisasi Peraturan Akademik dan Kemahasiswaan sebagai Upaya Penguatan Budaya Akademik Mahasiswa Politeknik Kampar - Belia Afifah; Fina Nasari; Dini Amalia Putri; Boris Kaido; Fajar Aga Wandana; Eka Erzalia; Suci Fitri Amalia (Lembaga Pengembangan Kinerja Dosen, 2026)
The socialization of academic and student regulations is a strategic initiative to strengthen academic culture among first-year students. This community engagement activity was conducted by a team of lecturers in collaboration with senior students to provide essential knowledge regarding academic regulations, scholarship schemes, point-based disciplinary systems, graduation requirements, and student policies from the beginning of the academic journey. The program took place on November 28, 2025, at Gedung Serba Guna of Politeknik Kampar, Bangkinang. An interactive dissemination approach was employed, consisting of structured presentations, open discussions, and question-and-answer sessions. The activity aimed to clarify institutional expectations and reduce misconceptions commonly encountered by new students. The results indicate a significant improvement in participants’ understanding of academic procedures, as reflected in constructive engagement, positive feedback, and focused inquiries on academic guidance mechanisms, scholarship eligibility, and students’ rights and responsibilities. This initiative is expected to serve as a sustainable academic development program that supports student preparedness, promotes responsible academic behaviour, and minimizes regulatory violations throughout the study period. Socialization; Academic Regulations; Student Regulations; Point-Based System; Academic Culture.